Environment Reporting in India: In Search of a Defining Philosophy - Dr. Silajit Guha (COMMUNICATION & JOURNALISM RESEARCH, 2012)
There is a kind of ideals and values of environmental journal- ism that every newsroom should commit to report; the values that exists independently of its value to humans. This must be a revelatory experience for anyone interested in the environment or in corporate regulation, and there must be an invaluable urge for environmental journalists to penetrate behind the veils of secrecy and obfuscation that surround so many environmental stories. While giving a closer look into the different types of environmental movements in India and many a shades in the movement for environment in terms of its ideological and political orientation, the researcher points out that newspapers content do not appear to have anything to do with the different shades of philosophy that guide environmental movements around the world. This apathy of treating environment as a phenomenon with a serious nterpretation for national polity, to translate the debate of using the country as a dumping ground by the west, to link the issue of fishing trawlers in the deep sea with the question of sea-resource depletion or food security are some of factors that speak of a greater malady associated with Indian environmental journalism.